The Interrelation Between The Declaration Of Independence Of Armenia And The Constitution Within The Paradigm Of State Sovereignty - Khalatyan, Artashes (NAS RA)
The scientific issue of this article is the analysis of two main constitutional acts of the Third Armenian Republic, the Declaration of Independence and the Constitution, as cornerstones of the sovereignty of the Armenian state. Particularly, using historical-legal, comparative and systemic methods of research, the author has presented theoretical and institutional landscape of interrelations between the Declaration of Independence, which is the institutional basis and historical symbol of regaining of sovereignty by the Armenian people, and the Constitution, which is a legal and political “roadmap” of functioning of a sovereign Armenian state. As a result, the author has substantiated, that during the evolution of the Armenian statehood the Declaration of Independence ceded its constitutional role to the Constitution, as after adoption the latter assumed the status of the prime regulator of social relations within the state. Accordingly, the author has presented plausible scientific evidence, claiming, that the Declaration of Independence has no autonomous existence within the legal system of Armenia, since the relevant (but not all) principles of organization of sovereign state, in pursuance of the Preamble of the Constitution, are incorporated in its body text, whereas the remaining postulates, which do not have legal meaning per se, remain solely as political provisions without legal effect. Notwithstanding all the above, the author has elaborated upon political and value significance of the Declaration of Independence, both before and after the Constitution’s adoption, negating any public debate, which aims at or results in confrontation between two main legal and political acts, effectuating the sovereignty doctrine of Armenia.
Keywords: Constitution